Pengembangan modul pembelajaran atletik berbantuan QR code - Hartoto, Muhammad; Mulyono, Dodik; Syafutra, Wawan (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
This study aims to develop an athletic learning module assisted by QR code for grade X students of MA Mutiara Al-Qur'an. The research method used was the research and development model of Dick and Carey with nine steps. Data collection techniques in research using interviews, observation, questionnaires. The data analysis technique used the steps of analyzing the validity of the media expert, getting a value of 87.03%, the linguist with a value of 82.14%, and the material expert getting a value of 95.83% so that from these results the validity of the module was categorized as very valid, then the practical questionnaire data analysis One to one and small group test students got a score of 87.22% so that the practicality of the athletic learning module assisted by the QR code for the tenth grade students of MA Mutiara Al-Qur'an was categorized as having very strong practicality.